Fiscal Decentralization: A Comparative Study Between South Korea And Indonesia - Hafiz, Muhammad; Frinaldi, Aldri; Magriasti, Lince (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Fiscal, administrative and political devolution from the center to lower levels of government has been widely advocated in both developed and developing countries. Fiscal decentralization implies more informed and more specific public local policies. Because fiscal decentralization can lead to more efficient provision of services and public goods to citizens and promote a better match between local government policies and citizens' needs. This study aims to compare the development of fiscal decentralization in South Korea and Indonesia. In OECD countries, one of which is South Korea, local governments spend more on housing and community development, the environment, culture, recreation and education. Meanwhile in Indonesia, personnel expenditure has the largest portion compared to other types of expenditure. So that the use of regional funds is still not optimal for improving the quality of life of the community.